Transformations of maternity´s meaning and experience of black, indigenous and half-blood women of south-western Colombia - Posso Quiceno, Jeanny Lucero (Sociedad y Economía, 2010)
This article proposes to study as there interpret and live through the mothering black, indigenous and half-caste women of the south Colombian west of two generational cohorts of municipalities placed in the north of the Cauca and the south of the Valle. It is a question of establishing the contrast between the traditional visions of the mothering that come from the prescriptions of the social groups of origin of the women and the new expressions and experiences of the mothering. The text divides in three parts, first a theoretical review is made on the concepts of gender and mothering, then present the results of the research and finally they present some conclusions.